MENELUSURI KETERKAITAN ANTARA KOMPETENSI DIGITAL DAN KEBIJAKAN PEMBELAJARAN DIGITAL TERHADAP DIGITAL CITIZENSHIP MAHASISWA PTKI INDONESIA - Alfarizi, Muhammad; Ngatindriatun (Balai Diklat Keagamaan Bandung, 2024)
The post-COVID-19 education transformation has accelerated the adoption of digital solutions, giving rise to the concept of digital citizenship as an essential dimension of responsible citizenship. Islamic Higher Education Institutions (PTKI) in Indonesia have undergone significant changes with the integration of technology in learning. Challenges of privacy, security, and responsible digital behavior need to be addressed holistically. Digital competencies, including data literacy, communication, digital content creation, and problem-solving, are key to shaping digital citizenship. In-depth research on the relationship between digital competencies and digital citizenship among PTKI students is necessary to formulate effective strategies in education. This study aims to analyze the relationship between digital competencies of Indonesian Islamic higher education students developed through the educational process and their capabilities in responsible digital citizenship. The study involves 200 PTKI students obtained through convenience sampling. Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique is employed. The research highlights the crucial role of problem-solving, data literacy, communication, collaboration, digital content creation, and digital learning policy in shaping digital citizenship among PTKI students. Integrating these skills into the curriculum is vital for cultivating a meticulous, skilled, and responsible digital generation. Challenges of data privacy and security necessitate a holistic approach with clear digital learning policies. The study underscores the need for students and education stakeholders to adapt to digital competencies and citizenship. The DigComp digital competency framework serves as a crucial reference, while effective learning includes online module training, cybersecurity workshops, and ethical digital behavior campaigns. In conclusion, PTKI and the Ministry of Religious Affairs need to synergize to strengthen religious education in the digital era.